Skills and the Labor Market in a New Era : Managing the Impacts of Population Aging and Technological Change in Uruguay - Apella, Ignacio; Rofman, Rafael; Rovner, Helena (Washington, DC: World Bank, 2020)
Uruguay faces medium- and long-term challenges associated with two global megatrends: population aging and technological change. These two megatrends have been developing for some time, but policy responses have been late or inadequate in many cases. Trying to delay them--by promoting higher fertility or enforcing restrictions on the adoption of new technologies--would probably be ineffective but also ill-advised, as these trends are generating important opportunities to increase production and welfare. The objective of this book is to identify these opportunities, as well as the challenges that population aging and technological change pose for the Uruguayan economy and to determine how they can be addressed through better-designed public policies, with a focus on the development of new skills that increase workers’ productivity.